2019
DOI: 10.18697/ajfand.86.17140
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions towards genetically modified foods in Zimbabwe

Abstract: Controversy regarding use of genetically modified (GM) foods still persists in both developing and developed worlds. Proponents of genetically engineered foods argue this is a sustainable solution to resource-limited settings where food insecurity continues to increase. However, in this pertinent debate, there is deficiency of knowledge on the opinion of the general public from resource-limited African communities. The aim of this paper is to describe the general public's level of knowledge and perceptions tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Many of these studies have found that while consumers are aware of GM foods, they lack detailed information about them and are heavily impacted by mass media, which emphasizes the negative features of GM foods. As a result, it is vital to assess the link between consumers' understanding of genetically modified foods and their attitudes and actions, which will aid in ensuring consumer safety and providing managerial insights to the food business [6,15,16].…”
Section: The Role Of Knowledge In Determining Perceived Benefits and ...mentioning
confidence: 99%
“…Many of these studies have found that while consumers are aware of GM foods, they lack detailed information about them and are heavily impacted by mass media, which emphasizes the negative features of GM foods. As a result, it is vital to assess the link between consumers' understanding of genetically modified foods and their attitudes and actions, which will aid in ensuring consumer safety and providing managerial insights to the food business [6,15,16].…”
Section: The Role Of Knowledge In Determining Perceived Benefits and ...mentioning
confidence: 99%
“…Evidence from the literature shows that the more aware and knowledgeable the public members are, the more likely they are to be more receptive to GM technology and food. For example, Changwena et al (2019) reported that consumers with increased knowledge of genetic engineering were more receptive to GMFs in their diets. Deffor (2014) calls for promoting awareness and knowledge, pointing to its necessity in the acceptability of GM technology and foods.…”
Section: Farmers' Inadequate Knowledge Of Gmfs Is Associated With The...mentioning
confidence: 99%
“…For example, Karau et al (2020) reported that although most of the respondents in their study (89.3%) said they were aware of GMOs, they failed to demonstrate this awareness because a significant number of them provided misleading information that they were aware of farmers who grew GM crops such as maize, tomatoes, and bananas in Kenya. A related case was reported by Changwena et al (2019), who assessed public knowledge and perception of GMFs. They reported that only 38% of their respondents could provide simple, meaningful definitions of GMOs when required despite most of them reporting to be aware.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that, in general, better knowledge about GMOs leads to more positive perceptions and vice versa [30][31][32][33] and knowledge levels can be used to predict GMO perceptions. 34 Consumers' lack of knowledge about GM technology has been found in both developing and developed countries 33,[35][36][37][38][39] and educating the general public about GM technology increases willingness-to-eat GM products. 34 In Europe, lawmakers intend to act on the precautionary principle and GM foods are considered case by case, 40,41 whereas, in the USA, GM products are "substantially equivalent" to non-GMOs and "generally recognised as safe".…”
Section: Introductionmentioning
confidence: 99%